Community infrastructure to boost social relations: a systematic review. (13th November 2019) - Bagnall, A; South, J; Southby, K; Di Martino, S; Pilkington, G; Mitchell, B; Pennington, A; Corcoran, R
Abstract: Background: 'Boosting social relations' in communities has been identified as a priority UK policy-related topic. An earlier scoping review identified evidence gaps in social relations & community infrastructure. We undertook a mixed method systematic review on this topic, which has potential for immediate practical impact. Methods: A comprehensive search included 11 databases (1997-2017), grey literature and citation checking. Studies of interventions to improve or make alternative use of community or neighbourhood places, reporting outcomes of social relations, community wellbeing & related concepts were included. Established validity checklists. Qualitative data was synthesised thematically and a narrative synthesis was produced. GRADE and CERQual approaches were used to rate the overall strength of evidence for each outcome. Results: 51 included studies, mostly of poor to moderate quality, and mostly qualitative, provided moderate evidence that: Community hubs may promote social cohesion, increase social capital and build trust, widen social networks, increase interaction, and increase knowledge or skills; Changes to neighbourhood design may positively affect sense of belonging and pride in a community; Green and blue space interventions that provide the opportunity to participate in activities or meetings may improve social interactions, increase social networks, bonding and bridging social capital, physical activity and healthy eating, and improve people's skills and knowledge. There were also common themes relating to facilitators and barriers to successful interventions. Conclusions: There is moderate evidence that a range of intervention approaches to community infrastructure can boost social relations and community wellbeing. Future research should prioritise high quality evaluations using repeated measures and validated tools, and robust and credible qualitative evidence. Key messages: There is moderate evidence that a range of intervention approaches to community infrastructure can boost social relations and community wellbeing. Community hubs may promote social cohesion, increase social capital and build trust, widen social networks, increase interaction, and increase knowledge or skills.